A Typical Simulation of a 3-KW Stirling Engine - Ding Guozhong; Yan Jiwei; Shu Shuiming; Duan Chen (Institute of Advanced Engineering and Science, 2012)
Stirling engine is being received more and more attention with the development of renewable energy utility. The paper described the design and simulation of a 3-KW Stirling engine based on a testing V-type machine while in the process of manufactured at the Huazhong University of Science and Technology. The engine was driven by solar energy. Based on the testing machine, the heater model of variable heat source, regenerator model and complete appliance model were built, and the thermal performance was simulated and shown under a typical sunlight in the area of Wuhan. The results suggested that the output power curve of Stirling engine appeared as the shape of a saddle in consideration that the radiant energy density of solar energy was non-constant, and electrical heating was employed to serve as the auxiliary heat source. There was about 1.83 KW output work of the manufactured engine during the simulation, and the effective efficiency was about 25.4%. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1405